2005
DOI: 10.1051/0004-6361:20053083
|View full text |Cite
|
Sign up to set email alerts
|

What determines the radio polar brightening?

Abstract: Abstract. In order to explain the bright patches of emission near the poles of 17 GHz solar maps, we have applied a previously developed atmospheric model based on radio observations. This 2-D model, which includes spicules, yields results in good agreement with brightness temperature values at the disk center, radius, and limb brightening 17 GHz observations at equatorial and intermediate regions. Nevertheless, the intensity of discrete bright patches observed near the poles in 17 GHz maps (as bright as 40% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
(26 reference statements)
0
13
0
3
Order By: Relevance
“…The simulations were based on the temperature and density distributions proposed in the SSC atmospheric model (Selhorst et al 2005a), with modifications to include a coronal hole atmospheric model and magnetic loops as the sources of the radio bright patches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulations were based on the temperature and density distributions proposed in the SSC atmospheric model (Selhorst et al 2005a), with modifications to include a coronal hole atmospheric model and magnetic loops as the sources of the radio bright patches.…”
Section: Discussionmentioning
confidence: 99%
“…The atmospheric model Selhorst et al (2005a) proposed an atmospheric model (hereafter referred to as the SSC model) with the distributions of temperature and density (electron and proton) as a…”
Section: Modeling Coronal Holes and Polar Bright Patchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations conducted by Selhorst et al (2005) showed that the spicules could modulate the morphology of the limb brightening profile. However, the empirical chromospheric model used by Selhorst et al (2005) is not necessarily a good approximation for the physical conditions in the lower chromosphere (Carlsson & Stein 2002;De la Luz et al 2011) when considering a fully ionized chromosphere. Observations of the solar limb at Hα (Skogsrud et al 2014) clearly show spicules in the upper chromosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the fine structure involved in the quiet Sun emission (spicules) and its relation to the limb brightening at millimeter wavelengths was discussed in the first semi-empirical models (Fuerst et al 1979;Ahmad & Kundu 1981). Further investigations conducted by Selhorst et al (2005) showed that the spicules could modulate the morphology of the limb brightening profile. However, the empirical chromospheric model used by Selhorst et al (2005) is not necessarily a good approximation for the physical conditions in the lower chromosphere (Carlsson & Stein 2002;De la Luz et al 2011) when considering a fully ionized chromosphere.…”
Section: Introductionmentioning
confidence: 99%